The creativity of imitation in remake videos. (July 2019) - Hobbs, Renee; Friesem, Yonty
A growth in the popularity of remix culture has led to the phenomenon of people creating videos that explicitly imitate or copy an original work. In order to explore the potential educational value of the remake video phenomenon, we conducted a content analysis of 93 videos that were inspired by "Love Language, " a sentimental narrative video that features the themes of budding romance and disability awareness. Some remake videos attempt to closely match the original work in both content and form. Other producers are inspired by the original work and create remakes that diverge considerably in content, format, and cinematograph. Using content analysis, we examined the ratio of imitation to originality for content, form, and cinematographic variables. Most remakes include careful imitation of narrative story elements, with evidence of originality found in the depiction of social relationships. Format and cinematographic codes reveal less strict imitation. The production of remake videos may enhance media literacy competencies by offering a means for young media makers to develop creative skills through strategic imitation.